Personal psycological preparation and diversity - Vladimir Medina Vaillant (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
The athlete preparation to face the extreme and different conditions at trainings and competitions increase the importance of his formation to achieve the best possible results in correspondence with the present sport activity. The base of the sport improving in the athlete preparation is mainly at the psychological preparation, an athlete can be well prepared in several aspects, but he wouldn't win in the contest if he has not developed, in the proper level, the demanding psychological functions and feature. Taking into account the difficulties detected at trainings and competitions in connection with the athlete psychological preparation when assimilating and putting into practice the received contents, we propose the present work to be used as a developing tool by trainers in order to get the best athlete preparation considering the present training managements. Among the investigation methods used in the work are the observation, about how the preparation process is developed, as well as its weakness and strengths; analysis and synthesis for the valuation of the theories and consulted authors. From the empiric level the used methods are the interview and the survey to know about the work regularities, the training plans drawing up, the athlete preparation plan, as well as the trainer's work conception.